Intrinsic neurons in the duck choroid are contacted by CGRP-immunoreactive nerve fibres: Evidence for a local pre-central reflex arc in the eye - Schrödl, Falk; Schweigert, Matthias; Brehmer, Axel; Neuhuber, Winfried (Experimental Eye Research, 2001)
Intrinsic choroidal neurons represent peripherally displaced autonomic nerve cells supposed to work as a local integrative network similar to the enteric nervous system, to control choroidal vasculature and stromal smooth muscle. A typical feature of such intramural neuronal networks is the innervation by primary afferent collaterals expressing peptides, e.g. CGRP. The present study was aimed at determining primary afferent contacts on nitrergic intrinsic choroidal neurons (ICN) in the duck eye. In addition, a sympathetic innervation of ICN was assessed. Choroids were immunohistochemically processed for the following markers: Neuronal nitric oxide synthase (nNOS), galanin (GAL), calcitonin gene-related peptide (CGRP), and tyrosine hydroxylase (TH). For evaluation, fluorescence as well as confocal laser scanning microscopy were used. For electron microscopy, immunoperoxidase staining for CGRP in combination with NADPH-diaphorase histochemistry was applied. ICN immunoreactive for nNOS or GAL spread over the entire choroid, although they were concentrated in an equatorial zone passing obliquely from naso-cranial to temporo-caudal. About 40% of ICN showed dose relationships with CGRP-immunoreactive nerve fibres, originating most likely in the trigeminal ganglion, as seen in the fluorescence and confocal laserscanning microscope. These appositions could be ultrastructurally defined as both synapses and close contacts without synaptic specialization. Some ICN endowed with CGRP-positive fibres also received TH-immunoreactive boutons. CGRP-immunoreactive profiles were also detected in close relationship to choroidal non-vascular smooth muscle cells and collagen fibres connected to them. In many instances, they were intercalated between smooth muscle cells and processes of ICN forming triads. These results suggest that ICN, similar to other intramural autonomic systems integrate signals from trigeminal primary afferent collaterals. The 'sensory' terminals of these primary afferents may be located in the anterior eye segment but also within the smooth muscle stroma of the choroid itself. Thus, ocular homeostasis may be regulated via intraocular pre-central reflexes which are probably subject to sympathetic modulation. © 2001 Academic Press.
Keywords: Confocal laserscanning microscopy; Electron microscopy; Nitric oxide; Parasympathetic nerve; Sympathetic nerve; Trigeminal primary afferents